2004
DOI: 10.1074/jbc.m405363200
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonicity-induced Exocytosis of the Skate Anion Exchanger skAE1

Abstract: Upon hypotonic volume expansion, skate erythrocytes lose solutes via a pathway that requires participation of anion exchangers (AEs). Three skate AE isoforms (skAEs) are expressed, and at least skAE1 has been shown to mediate this effect when expressed in oocytes. Under isoosmotic conditions, only a small fraction of skAE1 is expressed on the external plasma membrane. Under these conditions, a portion of skAE1 may be found in non-ionic detergent-insoluble regions. However, the detergent-insoluble material is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…A similar expression pattern for flotillin was reported when PC12 cells were cultured in vitro (28). Expression pattern of flotillins and caveolins in type I and II cells might reflect the specific roles of these proteins in different cells, although there are a number of cells expressing both caveolins and flotillins, such as skate erythrocytes (29) and neonatal rat cardiomyocytes (30). In addition, flotillin-1 and -2 were enriched on the plasma membrane and lamellar bodies, indicating their possible roles in membrane trafficking.…”
Section: Discussionsupporting
confidence: 70%
“…A similar expression pattern for flotillin was reported when PC12 cells were cultured in vitro (28). Expression pattern of flotillins and caveolins in type I and II cells might reflect the specific roles of these proteins in different cells, although there are a number of cells expressing both caveolins and flotillins, such as skate erythrocytes (29) and neonatal rat cardiomyocytes (30). In addition, flotillin-1 and -2 were enriched on the plasma membrane and lamellar bodies, indicating their possible roles in membrane trafficking.…”
Section: Discussionsupporting
confidence: 70%
“…Other evidence cited in favour of a role for the anionexchanger in volume-sensitive taurine transport in fish red blood cells are the findings that cell swelling increases the binding of DIDS to the band 3 protein and stimulates the phosphorylation of the exchanger [73]: these results could be explained by the fact that cell swelling induces the movement of AE1 from an intracellular pool to the plasma membrane [74]. In addition, it has been reported that osmotic swelling induces the formation of band 3 tetramers in skate erythrocytes [75,76].…”
Section: The Relationship Between Volume-sensitive Taurine Transport mentioning
confidence: 99%
“…This appearance is strongly associated with volume expansion under these conditions. 39 AEs are shown to participate in the efflux of solutes during regulatory volume decreases. In particular, AEs appear to contribute to the loss of aurine from red blood cells of a number of species.…”
Section: Various Fish Speciesmentioning
confidence: 99%